2011
DOI: 10.1007/s12200-011-0207-0
|View full text |Cite
|
Sign up to set email alerts
|

Dye-sensitized solar cells based on ZnO nanotetrapods

Abstract: In this paper, we reviewed recent systematic studies of using ZnO nanotetrapods for photoanodes of dye-sensitized solar cells (DSSCs) in our group. First, the efficiency of power conversion was obtained by more than 3.27% by changes of conditions of dye loading and film thickness of ZnO nanotetrapod. Short-circuit photocurrent densities (J sc ) increased with the film thickness, J sc would not be saturation even the film thickness was greater than 35 μm. The photoanode architecture had been charactered by good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…It should be noted that besides the widely reported arrays of 1D nanowires, nanopillars, nanorods, nanotubes, and nanofibers, recent studies have demonstrated that solar cells based on nanohole arrays (Fig. 19a-b), [104][105][106][107] zigzag structure arrays, 108 branched nanowire arrays or nanoforests, 77,78 nanocrystallite aggregates, 81,83 nanograting arrays, 109 nanospike arrays, 110 and nanocomposites of 0D and 1D materials, 68,69,75,[85][86][87]98 etc. also show superior light trapping capability and thus, higher power conversion efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that besides the widely reported arrays of 1D nanowires, nanopillars, nanorods, nanotubes, and nanofibers, recent studies have demonstrated that solar cells based on nanohole arrays (Fig. 19a-b), [104][105][106][107] zigzag structure arrays, 108 branched nanowire arrays or nanoforests, 77,78 nanocrystallite aggregates, 81,83 nanograting arrays, 109 nanospike arrays, 110 and nanocomposites of 0D and 1D materials, 68,69,75,[85][86][87]98 etc. also show superior light trapping capability and thus, higher power conversion efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Fig. 14, a variety of 3D nanostructures such as ZnO nanotetrapods, 74,75 branched ZnO nanowires, 76 ZnO or TiO 2 nanoforests, 77,78 dendritic ZnO nanowires, 79 ZnO nanoflowers, 80 ZnO aggregates, 81 TiO 2 nanotubes on titanium mesh, 82 nanoporous TiO 2 spheres, 83 and hollow TiO 2 hemispheres 84 have been reported. It was found that these 3D nanostructure photoelectrodes can indeed improve photovoltaic performance.…”
Section: Cds/cdte Nanopillar Based Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, one of the solutions to these problems is to obtain microstructured systems assembled from nanotubes, nanoplates and etc. [4,5,[12][13][14][15]. Such an approach will provide the material with a developed surface, a large particle size that is comparable to the wavelength of visible light, can increase the efficiency of light collection due to the effective scattering effect.…”
Section: Introductionmentioning
confidence: 99%
“…Owning to the easy crystallization and anisotropic growth, various ZnO nanostructures such as nanoparticles [1][2][3], nanorods [4][5][6][7][8], nanotubes [9][10][11][12], nanoflowers [13], nanosheets [14], tetrapods [15], nanotrees [16], nanowire-nanosheet [17], nanoforest [18], nanodendrite/nanoparticle composite [19] and multilayer nanowires [20] have been reported in DSSCs. Researchers generally focused on the design of various nanostructured semiconducting materials with emphasis on optimizing dye loading, and less on ZnO material properties themselves such as defect concentration.…”
Section: Introductionmentioning
confidence: 99%